2g-5=

Simple and best practice solution for 2g-5= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2g-5= equation:


Simplifying
2g + -5 = 0

Reorder the terms:
-5 + 2g = 0

Solving
-5 + 2g = 0

Solving for variable 'g'.

Move all terms containing g to the left, all other terms to the right.

Add '5' to each side of the equation.
-5 + 5 + 2g = 0 + 5

Combine like terms: -5 + 5 = 0
0 + 2g = 0 + 5
2g = 0 + 5

Combine like terms: 0 + 5 = 5
2g = 5

Divide each side by '2'.
g = 2.5

Simplifying
g = 2.5

See similar equations:

| 0.8z+3.74=z+1.5 | | 4(9.7-8.1)=(9.7)-(8.1) | | 75=3-10t-3+6t | | .75(x-5)=12 | | .5x+1=.5x-1 | | .75w-.50w-4=12 | | 8(x+2)=2(4x+4)+8 | | (-3a^2b^3)(-4a^4b^2)= | | 3(t-1)=9+2 | | 596=-8x | | .75(x+5)=12 | | -9x-21=35x | | m-1=-2-9 | | 5w^2-23w-42=0 | | s=L-rL | | 2x-36=5(x+3) | | 100=20t+5t^2 | | 4-5X=59 | | 4x-3x=1x | | 6a^2-5a-4=0 | | 5x=6x+31 | | 25.00x=4.50 | | 3y-2+6x=0 | | 2x-6=3x+1-x-2 | | 4x^2+4x=9 | | 2(x+4)-5=2x+13 | | n+5=9+2n-3-8 | | .5(4x-10)=52+3x | | 69=3v | | 3x-6+x+8=42 | | 5xy^2+3xy^2= | | -5w^2+23w-42=0 |

Equations solver categories